PENGARUH DESAIN CAFE UNTUK MENARIK PARA PENGUNJUNG TERHADAP PENINGKATAN PENGUNJUNG STUDY KASUS PADA CAFE RAHAYU & RESTO DI SEI RAMPAH KABUPATEN SERDANG BEDAGAI - Tomy Agustiawan; Muhammad Rahmat (Universitas Islam Sumatera Utara, 2021)
This study aims to determine the effect of cafe design on increasing visitors to Cafe Rahayu Resto in Sei Rampah, Serdang Bedagai Regency. The sampling technique used is the random sampling method, which is taking samples from the population at random without regard to the existing strata in the population of 84 people. Methods of data collection using a questionnaire. In the partial hypothesis test (t test) the cafe design variable has a positive and significant effect on increasing visitors with a t count t table (12.766 1.989) and a significant value of 0.000 0.05. The results of the determination test obtained an R Square value of 0.665, meaning that the variable increase in visitors can be explained by 66.5% by the cafe design variable, while the remaining 33.5% is explained by other variables not included in this study.